The Influence of Entrepreneurial Orientation on MSME Business Performance in Bekasi City - Mediany Kriseka Putri; Muhammad Rizal Affandi (Indonesian Journal of Business Analytics, 2024)
This study aims to investigate the influence of entrepreneurial orientation including innovativeness, proactiveness, and risk-taking on the business performance of MSMEs in Bekasi City. Using a quantitative approach, a structured survey was conducted among 383 MSME owners. Data were analyzed through covariance-based structural equation modeling (SEM) using AMOS 29.0 software. The results showed that entrepreneurial orientation has a positive and significant effect on MSME performance. The findings underscore the key factors for business success, namely innovation, proactivity, and risk-taking. This research offers valuable insights for business owners and stakeholders to encourage entrepreneurial attitudes, thereby enhancing the growth and sustainability of MSMEs. The ultimate goal of this research is to provide practical guidance and strategies for more effective MSME development in the future.